Caracterização de argamassas históricas: estudo de caso do hospital do Totoró de Currais Novos/RN - Cruz, Maisa Dantas Silveira (Universidade Federal Rural do Semi-Árido, 2019)
The search for conservation of cultural heritage has been more and more evidenced and fundamental, in order to maintain and preserve the identity of a society. Historical buildings are integral parts of this heritage and the best way to preserve them is by analyzing and knowing their materials and methods used during the construction period, in order to make a more harmonious and efficient restoration with materials similar to the original ones. In this context, this work aims to characterize the lining mortars of the former Totoró Hospital, in the city of Currais Novos / RN. To do this, an on-site visit was carried out for a visual observation and photographic registration of the building, thus collecting samples of coating mortars for subsequent physical-chemical characterization by means of visual analysis and analytical techniques performed in the laboratory. of water absorption by immersion, particle size and determination of the binder content by acid attack. Based on the analyzes, it was observed that the mortars studied were composed of lime and sand (of the thick type), having significant rates of absorption and having the agglomeration / aggregate ratio of 1: 4 for sample A04, 1: 6 for samples A01, A02 and A03, and 1: 7 for samples A05 and A06. In this way, from the information discovered through the laboratory analysis of the mortars existing in that building, it is possible to design a mortar of compatible reconstruction for the accomplishment of the conservation of this historical building, thus contributing to the project of preservation and restoration of this monument existing in the City Hall of the city together with the Federal University of Rio Grande do Norte, Currais Novos Campus.
Monografia
Keywords: Edificações históricas; Revestimentos; Argamassa de cal; Caracterização da argamassa; Restauro; Historical buildings; Coatings; Lime mortar; Characterization of the mortar; Restoration; ENGENHARIAS::ENGENHARIA CIVIL